Modulation of Yorkie activity by alternative splicing is required for developmental stability. - Srivastava, D.; de Toledo, M.; Manchon, L.; Tazi, J.; Juge, F. (The EMBO Journal, 2021)
The Hippo signaling pathway is a major regulator of organ growth, which controls the activity of the transcription coactivator Yorkie (Yki) in Drosophila and its homolog YAP in mammals. Both Yki and YAP proteins exist as alternatively spliced isoforms containing either one or two WW domains. The biological importance of this conserved alternative splicing event is unknown. Here, we identify the splicing factor B52 as a regulator of yki alternative splicing in Drosophila and show that B52 modulates growth in part through modulation of yki alternative splicing. Yki isoforms differ by their transcriptional activity as well as their ability to bind and bridge PPxY motifs-containing partners, and can compete in vivo. Strikingly, flies in which yki alternative splicing has been abrogated, thus expressing only Yki2 isoform, exhibit fluctuating wing asymmetry, a signal of developmental instability. Our results identify yki alternative splicing as a new level of modulation of the Hippo pathway, that is required for growth equilibration during development. This study provides the first demonstration that the process of alternative splicing contributes to developmental robustness.